Coronavirus: Older Persons With Cancer in Italy in the COVID-19 Pandemic - Fratino, Lucia; Procopio, Giuseppe; Di Maio, Massimo; Cinieri, Saverio; Leo, Silvana; Beretta, Giordano (Frontiers in Oncology, 2020)
Italy is the European country that was hit first and hardest by the COVID-19 epidemic. Since February 2020, the outbreak of the epidemic disease in Italy, with fatal outcomes in up to 10% of cases, made it urgent to implement extraordinary measures to avoid a breakdown of the universal Italian national health system. The update for April 1, 2020, in Italy recorded 102,669 confirmed COVID-19 cases, with a median patient age of 63 years. The deceased patients were older people (median age 80 years) and often had a cancer diagnosis (about 20%). Thus, in the extraordinary epidemiological scenario of the COVID-19 pandemic in Italy, older persons in cancer treatment are at particularly high risk of being severely affected by COVID-19. These people face a health- and economics-related emergency that also carries cultural and ethical implications. In accordance with the measures adopted by the Italian government to limit viral transmission, several associations of Italian oncologists have taken action to update Elderly Cancer Care programs. In view of the newly emerging needs, we herein outline practical suggestions aimed at guaranteeing the best continuity to elderly cancer patients.